Observed/revealed willingness to pay for QALYs in older adults: Evidence from planned commonly used surgical procedures. (2nd April 2020) - Walton, Surrey M.; Johnson, Tricia J.; Hohmann, Samuel; Garman, Andy N.
ABSTRACT: Objectives: Published estimates of willingness to pay (WTP) for quality adjusted life years (QALYs) based on elicited preferences vary widely, especially across health procedures. The study evaluated the revealed WTP for QALYs by older adult patients who paid fully out-of-pocket for common inpatient procedures in the United States. Methods: Patient-level discharge data were from academic medical center members of the University Health System Consortium Clinical Data Base from 2005 to 2015 (now Vizient) for patients who paid 'cash-in-full.' The median, 25th percentile, and 75th percentile of charges, payments, and payment to charge ratio were examined and combined with available measures on QALYs by procedure. Results: Among patients over age 50 from 22 academic medical centers there were 846 self-pay patients, and the majority were international. The mean out-of-pocket payment was $57731 and the payment to charge ratio was 0.53. For the five procedures with available QALYs, the lower bound median payment based estimates of WTP ranged from $2949 for PTCA to $15441 for replacement or repair of aortic valve. Conclusions: The study was designed to provide lower bound estimates of revealed preferences for QALYs. WTP and how it should intersect with payment policy remains an important area for future research.